Previous Exposure to the Fish Parasite Anisakis as a Potential Risk Factor for Gastric or Colon Adenocarcinoma. Issue 40 (October 2015) - Garcia-Perez, Juan Carlos; Rodríguez-Perez, Rosa; Ballestero, Araceli; Zuloaga, Jaime; Fernandez-Puntero, Belen; Arias-Díaz, Javier; Caballero, María Luisa
Abstract : Abstract: Anisakiasis is a global disease caused by consumption of raw or lightly cooked fish contaminated with L3 Anisakis spp. larvae. High rates of parasitization of fish worldwide make Anisakis a serious health hazard. In fact, anisakiasis is a growing disease in countries such as Spain, Italy, and Japan, where consumption of raw/marinated fish is high. Some parasitic infections have been recognized as a causative factor for human cancer. Suggested mechanisms include chronic inflammation elicited by the parasite, and a possible tumorigenic effect from certain parasitic secretions. Anisakis can produce persistent local inflammation and granuloma, and larvae have been incidentally found in gastrointestinal (GI) tumors. Our aim was to discover possible differences in the prevalence of unnoticed or asymptomatic previous Anisakis infection in GI cancer patients compared with healthy individuals. Serum levels of specific antibodies against Anisakis antigens were used as a reliable marker of previous contact with their larvae. Ninety-four participants without a previous history of Anisakis infection were prospectively allocated into 1 of 2 groups: 47 patients with GI cancer and 47 controls. Specific IgE, IgA1, and IgG1 against the Anisakis recombinant antigens Ani s 1, Ani s 5, Ani s 9, and Ani s 10 were determined by an ELISA assay. The ratio of positivity to sIgA1, rAni s 1, or rAni s 5 was significantly higher in the cancer patients than in the controls (38.30% vs 6.38%, P  < 0.001) and (42.55% vs 10.64%, P  < 0.001, respectively). When disaggregated by type of tumor, the patients with gastric cancer showed a higher proportion of positive results for sIgA1 to rAni s 1 ( P  < 0.001), whereas a higher proportion of colon cancer patients were shown to be positive for sIgA1 to both rAni s 1 ( P  < 0.05) and rAni s 5 ( P  < 0.01). Earlier Anisakis infection might be a risk factor for the development of stomach or colon cancer.